Transgenics in Fisheries: Perspectives,Priorities and Preparedness for India - Ayyappan, S; Gopalakrishnan, A (Indian Journal of Fisheries, 2011)
Transgenic technique provides a rapid and efficient method for fish improvementacross a wide range of species by direct gene manipulation. Gene transfer studiesin fishes have been initiated for developing some superior strains useful inaquaculture.Â  The most popular gene used in aquatic species is the growthhormone (GH) with an aim to enhance the growth rate of cultivable species.Transgenic ornamental fish popularly called as â€œglow fishâ€, harbouringfluorescent genes isolated from jellyfish has recently opened new possibilitiesfor producing new multi-coloured fluorescent fish. Transgenic fishes may alsobe used as â€œbio-reactorsâ€ to produce pharmaceuticals. Although this potential isbeing realized in crops, there has been no commercial use of genetically modifiedorganisms (GMOs) in aquaculture. Even though, the bio-safety framework inIndia surrounding the GMOs has been fabricated mainly to include agriculturallyimportant transgenic plants and hygienically important transgenic pathogens,the guidelines and rules emphasize the need for adequate safety measures aswell as assessing the economic viability of the transgenic organisms includingfish before large scale field trials are conducted. The research on fish transgenicsin India is relatively recent and the efforts in these lines are discussed.Transgenics as an emerging discipline will have an important role to play infuture in India also for increasing aquaculture productivity and for conservationand management of natural fishery. The paper is concluded with a set ofrecommendations aimed at best practice for safe use of transgenic fish in India.